5-HT3 and 5-HT4 antagonists inhibit peristaltic contractions in guinea-pig distal colon by mechanisms independent of endogenous 5-HT - Sia, Tiong C.; Whiting, Malcolm; Kyloh, Melinda; Nicholas, Sarah; Brookes, Simon J.; Oliver, John; Dinning, Phil; Wattchow, David A.; Spencer, Nick J. (Frontiers in Neuroscience, 2013)
Recent studies have shown that endogenous serotonin is not required for colonic peristalsis in vitro, nor gastrointestinal (GI) transit in vivo. However, antagonists of 5-Hydroxytryptamine (5-HT) receptors can inhibit peristalsis and GI-transit in mammals, including humans. This raises the question of how these antagonists inhibit GI-motility and transit, if depletion of endogenous 5-HT does not cause any significant inhibitory changes to either GI-motility or transit? We investigated the mechanism by which 5-HT3 and 5-HT4 antagonists inhibit distension-evoked peristaltic contractions in guinea-pig distal colon. In control animals, repetitive peristaltic contractions of the circular muscle were evoked in response to fixed fecal pellet distension. Distension-evoked peristaltic contractions were unaffected in animals with mucosa and submucosal plexus removed, that were also treated with reserpine (to deplete neuronal 5-HT). In control animals, peristaltic contractions were blocked temporarily by ondansetron (1–10 μM) and SDZ-205–557 (1–10 μM) in many animals. Interestingly, after this temporary blockade, and whilst in the continued presence of these antagonists, peristaltic contractions recovered, with characteristics no different from controls. Surprisingly, similar effects were seen in mucosa-free preparations, which had no detectable 5-HT, as detected by mass spectrometry. In summary, distension-evoked peristaltic reflex contractions of the circular muscle layer of the guinea-pig colon can be inhibited temporarily, or permanently, in the same preparation by selective 5-HT3 and 5-HT4 antagonists, depending on the concentration of the antagonists applied. These effects also occur in preparations that lack any detectable 5-HT. We suggest caution should be exercised when interpreting the effects of 5-HT3 and 5-HT4 antagonists; and the role of endogenous 5-HT, in the generation of distension-evoked colonic peristalsis.